Pendampingan Penyusunan Rancangan Peraturan Daerah tentang Pencegahan dan Peningkatan Kualitas Perumahan Kumuh dan Permukiman Kumuh Kota Lhokseumawe - Nurhaslita Sari (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
Regional Regulation (Perda) concerning Prevention and Improvement of Quality of Slums and Slums is an instrument to prevent the growth and development of slums in livable housing and settlements and to improve the quality of housing and settlements that are indicated as slums to become livable. Regional regulations on the Prevention and Improvement of Quality of Slum Housing and Slum Settlements are expected to contain regulations as regulated in national legislation and are equipped with specific local content for each region and to assist the Regional Government in the drafting process of the Regulation on Prevention and Quality Improvement of Slums and Slum Settlements, the Government (in this case the Directorate of Settlement Development, Directorate General of Human Settlements, Ministry of Public Works) has prepared a Regional Regulation Model on the Prevention and Quality Improvement of Slums and Slums. The purpose of the drafting of this Perda Model is to provide references and examples of regulations on prevention and improvement of the quality of slums and slums that have accommodated various provisions in national legislation.